Accelerating Dissolution of CO2 in Brine by Enhancing Convective Mixing as a Potential Remediation Option. (July 2017) - Peters, Elisabeth; Salari, Joris; Neele, Filip
Abstract: This paper presents a study into the possibility to enhance dissolution of CO2 in brine using nanoparticles (NPs) as a remediation and/or mitigation option for unwanted migration of CO2 . The idea is to inject a homogeneous mixture of NPs and CO2 into the stored CO2 . The heavier NP-CO2 mixture spreads on the interface between the CO2 and brine. The heavier NPs move into the brine together with the CO2 and increase the density of the brine. This will enhance the process of convective mixing which increases the dissolution rate of CO2 . However, it was found that the method is inefficient in terms of the amount of NPs needed compared to the increase in CO2 dissolution. For example, to achieve an increase of 50% in the CO2 dissolution rate, 1 kg of NP is needed to dissolve 3 kg extra CO2 for an example case at 1 km depth. This makes the method unattractive both technically and economically: a large effort is required for engineering NPs with the correct properties, the risks associated are clogging and pressure increase, and the method is expensive.